PERFORMANS REPRODUKSI SAPI PESISIR DAN SAPI BALI . DI DAERAH INSEMINASI BUATAN KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Yendraliza Yendraliza (State Islamic University of Sultan Syarif Kasim Riau, 2005)
Th research rums to kn the comparison of Pesisir and Bali c ws reproductive perfvrmances in artificial nsem natlon ar a! Bayang Peslslr Selatan. Data was collected using sample accidental methode on 130 and 41msemmated Peslslr and Ball cows respectively. The data was analyzed using t and z tests. .. The. result ho.wed that the first se,rvice after calving rate and the calving interval ofPesisir and Bali cows weredl e ent highly. slgruficant but the calvmg rate are different significantly. The first service after calving rate ofPeslslr .and Balt cows are 268.7 and 211.86 days, and the calving interval of the are 545.12 and 500.63 days. respectively. Furthermore the calvmg rate ofthem are 73.07% and 50% and the pregnant periode are 277.39 and 278 days respectively.